Drug eluting stents: are human and animal studies comparable?. Issue 2 (1st February 2003) - Virmani, R; Kolodgie, F D; Farb, A; Lafont, A
Abstract : Animal models of stenting probably predict human responses as the stages of healing are remarkably similar. What is characteristically different is the temporal response to healing, which is substantially prolonged in humans. The prevention of restenosis in recent clinical trials of drug eluting stents may represent a near absent or incomplete phase of intimal healing. Continued long term follow up of patients with drug eluting stents for major adverse cardiac events and angiographic restenosis is therefore imperative.